Comparison of partial least squares and random forests for evaluating relationship between phenolics and bioactivities of Neptunia oleracea - Soo, Yee Lee; Mediani, Ahmed; Maulidiani, M.; Khatib, Alfi; Ismail, Intan Safinar; Zawawi, Norhasnida; Abas, Faridah (John Wiley and Sons Ltd, 2018)
BACKGROUND: Neptunia oleracea is a plant consumed as vegetable and used as folk remedy for several diseases. Herein, two regression models (partial least square, PLS and random forest, RF) in metabolomics approach were compared and applied for the evaluation of relationship between phenolics and bioactivities of N. oleracea. In addition, the effects of different extraction conditions on the phenolic constituents were also assessed by pattern recognition analysis.